A atividade confiscatória do imposto territorial rural (ITR): uma afronta ao direito fundamental do não confisco - Rosa, Marcus Vinícius Sousa (2012)
The Tax on Rural Property (ITR), constitutionally provided and regulated by Law 9.393/96, has rates ranging from 0.03 to 20%, applied to the value of rural land. What we intend to unveil in the present study is that the rate of 20% tax ceases to have effect and becomes confiscation activity prohibited by the Constitution of 1988 in its article 150, item IV.Apresenta is therefore a stir caused by the absence of constitutional legislation, which demarcate a boundary between what is considered a tribute and what comes to be able to fit confisco.Para or not the ITR and its rate of 20% on the land, it is imperative to check the current forms of distinction between what you consider tax and confiscate. Finally, there is a fine line between tax and confiscate? Or what differentiates these practices would be an abyss? What really noticed is that the tax burden is overwhelming in this country, generating, in Brazil, the impression of no limits for the recovery of tributos.Ocorre that limit the collection of taxes there is exaggerated in the Constitutional text of 1988, more precisely in the art. 150, section IV, which prohibits the confiscation. However, this clause of the Constitution by the majority errs by not providing, to the taxpayer, parameters that allow the correct view of what will be confiscated, causing you the feeling of abandonment before the voracity state.